Closing the Racial Discipline Gap in Classrooms by Changing Teacher Practice. Issue 2 (1st June 2016) - Gregory, Anne; Hafen, Christopher A.; Ruzek, Erik; Mikami, Amori Yee; Allen, Joseph P.; Pianta, Robert C.
Abstract: Black students are issued school discipline sanctions at rates higher than members of other racial and ethnic groups, underscoring the need for professional development that addresses this gap. In 86 secondary school classrooms, a randomized controlled trial examined the effects of a 2-year teacher-coaching program, My Teaching Partner Secondary (MTP-S). Results from the second year of coaching and from the year after coaching was discontinued replicated previous findings from the first year of coaching—intervention teachers had no significant disparities in discipline referrals between Black students and their classmates, as compared with teachers in the control condition, for whom racial discipline gaps remained. Thus, MTP-S effects were replicated in the second year of coaching and maintained when coaching was withdrawn. Mediational analyses identified mechanisms for these effects; Black students had a low probability of receiving disciplinary referrals with teachers who increased skills to engage students in high-level analysis and inquiry.